Elevated levels of circulating CDH5 and FABP1 in association with human drug‐induced liver injury. (22nd June 2016) - Mikus, Maria; Drobin, Kimi; Gry, Marcus; Bachmann, Julie; Lindberg, Johan; Yimer, Getnet; Aklillu, Eleni; Makonnen, Eyasu; Aderaye, Getachew; Roach, James; Fier, Ian; Kampf, Caroline; et al.
Abstract: Background & Aims: The occurrence of drug‐induced liver injury (DILI) is a major issue in all phases of drug development. To identify novel biomarker candidates associated with DILI, we utilised an affinity proteomics strategy, where antibody suspension bead arrays were applied to profile plasma and serum samples from human DILI cases and controls. Methods: An initial screening was performed using 4594 randomly selected antibodies, representing 3450 human proteins. Resulting candidate proteins together with proposed DILI biomarker candidates generated a DILI array of 251 proteins for subsequent target analysis and verifications. In total, 1196 samples from 241 individuals across four independent cohorts were profiled: healthy volunteers receiving acetaminophen, patients with human immunodeficiency virus and/or tuberculosis receiving treatment, DILI cases originating from a wide spectrum of drugs, and healthy volunteers receiving heparins. Results: We observed elevated levels of cadherin 5, type 2 (CDH5) and fatty acid‐binding protein 1 (FABP1) in DILI cases. In the two longitudinal cohorts, CDH5 was elevated already at baseline. FABP1 was elevated after treatment initiation and seemed to respond more rapidly than alanine aminotransferase (ALT). The elevations were verified in the DILI cases treated with various drugs. In the heparin cohort, CDH5 was stable over time whereas FABP1 was elevated. Conclusions: These results suggest that CDH5 may have value as a susceptibility marker for DILI. FABP1 was identified as a biomarker candidate with superior characteristics regarding tissue distribution and kinetics compared to ALT but likely with limited predictive value for the development of severe DILI. Further studies are needed to determine the clinical utility of the proposed markers.